ANALYSIS OF THE EFFECT OF JOB INSECURITY AND WORK ENVIRONMENT PSYCHOLOGY ON TURNOVER INTENTION - Marintha Silva; Laura Syahrul; Harif Amali Rivai (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
High turnover intention in an organizations is a wonder that regularly happens. Turnover intention refers to an individual assessment of the continuation of a relationship with an organization that has not yet been acknowledged through leaving the organizations. Numerous things can be the reason for somebody find employment elsewhere. In this research work engagement, job insecurity, and psychological work environment found to significantly affect turnover intention of health workers, and job insecurity and psychological work environment found to significantly affect work engagement. This research also found the mediation effect of work engagement on the correlation from psychological work environment and turnover intention and also the mediation effect of work engagement on the correlation from job insecurity and turnover intention.